ERK Signals: Scaffolding Scaffolds? - Casar, Berta; Crespo, Piero (Frontiers in Cell and Developmental Biology, 2016)
ERK1/2 MAP Kinases become activated in response to multiple intra- and extracellular stimuli through a module composed of sequential tiers of cytoplasmic kinases. Scaffold proteins regulate ERK signals by connecting the different components of the module into a multi-enzymatic complex by which signal amplitude and duration are fine-tuned, and also provide signal fidelity by isolating this complex from external interferences. In addition, scaffold proteins play a central role as spatial regulators of ERKs signals. In this respect, depending on the subcellular localization from which the activating signals emanate, defined scaffolds specify which substrates are amenable to be phosphorylated. Recent evidence has unveiled direct interactions among different scaffold protein species. These scaffold-scaffold macro-complexes could constitute an additional level of regulation for ERK signals and may serve as nodes for the integration of incoming signals and the subsequent diversification of substrate specificity for the outgoing signals.